2016
DOI: 10.1038/ncomms11156
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing molecular vibrations in organic semiconductors by inducing strain

Abstract: Organic molecular semiconductors are solution processable, enabling the growth of large-area single-crystal semiconductors. Improving the performance of organic semiconductor devices by increasing the charge mobility is an ongoing quest, which calls for novel molecular and material design, and improved processing conditions. Here we show a method to increase the charge mobility in organic single-crystal field-effect transistors, by taking advantage of the inherent softness of organic semiconductors. We compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
116
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 41 publications
10
116
1
Order By: Relevance
“…A signature of new phenomena arising from strain effects was recently recognized by Frisbie and coworkers (28), who discovered a change in the work function of the organic semiconductor rubrene as a result of compressive and tensile strains. Takeya's group (29) reported on an increase in charge-carrier mobility upon the application of compressive strain, which they assigned to the reduction in the dynamic disorder as a result of minimizing molecular vibrations. Nickel and coworkers (30) found that pentacene crystals transition between two polymorphs to reduce the mechanical strain created in the lattice due to differences in contraction/expansion behavior of the film and the substrate.…”
Section: Significancementioning
confidence: 99%
“…A signature of new phenomena arising from strain effects was recently recognized by Frisbie and coworkers (28), who discovered a change in the work function of the organic semiconductor rubrene as a result of compressive and tensile strains. Takeya's group (29) reported on an increase in charge-carrier mobility upon the application of compressive strain, which they assigned to the reduction in the dynamic disorder as a result of minimizing molecular vibrations. Nickel and coworkers (30) found that pentacene crystals transition between two polymorphs to reduce the mechanical strain created in the lattice due to differences in contraction/expansion behavior of the film and the substrate.…”
Section: Significancementioning
confidence: 99%
“…Typical oligothiophenes are either fused systems [15] or end-capped by alkyl [16] or aromatic or polyaromatic groups in a symmetric [17] or asymmetric manner [18] manifesting vertically aligned face-to-face structure on the OFET surface. This structure is further modified by an additional molecular layer between electrodes and thiophene layer [19] or altered by external parameters such as externally induced uniaxial strain [20]. The structure of various oligothiophenes in OFETs has been resolved ex situ even in the monolayer level [16] but the effect of electric field in running OFETs, corresponding those observed for pentance [13], are not well reported.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Importantly, the intermolecular packing arrangement can be altered by internal/external lattice strain because of the weak intermolecular interactions, which allows for modulation of the organic charge transport in the crystal structures. [21][22][23][24][25][26][27][28] Understanding the correlation between molecular packing structures and charge transport properties would be useful for improving charge carrier mobility of organic semiconducting materials.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][29][30][31][32][33][34] Singlecrystal organic semiconducting materials should be used for reliable studies on the strain effects because they have longrange ordered and well-defined molecular-packing structures with no grain boundaries. [21][22][23][24][25][26] Note that the strain-induced electrical properties in polycrystalline organic thin films are mostly described by the response of grain boundaries rather than that of the materials themselves. [29][30][31][32][33][34] Studies using singlecrystal organic semiconductors have provided several important results with respect to the structure-electrical property relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation